2011
DOI: 10.1108/14691931111123430
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary disclosures of intellectual capital

Abstract: Purpose -This paper aims to investigate inter firm intellectual capital (IC) disclosures and its variations in top 20 listed pharmaceutical companies in India, study the category wise and element wise IC disclosures (ICD), find out the impact of ICD on the creation of IC in monetary terms, find out correlation between IC valuation and its disclosure, and test significance of correlation. Design/methodology/approach -This is an exploratory and empirical study of ICD by sample companies in 2009 using content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 41 publications
10
64
3
2
Order By: Relevance
“…They confirmed the findings in Kamath (). Applying Guthrie and Petty's () approach, Singh and Kansal () conducted research on the top 20 pharmaceutical companies in India. They focused on market‐to‐book value and found that RC was the most disclosed capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They confirmed the findings in Kamath (). Applying Guthrie and Petty's () approach, Singh and Kansal () conducted research on the top 20 pharmaceutical companies in India. They focused on market‐to‐book value and found that RC was the most disclosed capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 5 represents relational capital indicators for each category. Tai & Chen, 2009;Beattie & Thomson, 2007;Martin, 2000;Guthrie & Petty, 2000;Singh & Kansal, 2011;Cabrilo et al, 2009;Ortiz, 2009;Kim et al, 2010customer relationship Ramezan, 2011Bontis, 1998;Asonitis & Kostagiolas, 2010;Ortiz, 2009Customer complaint Ramezan, 2011Cabrilo et al, 2009;Wall, 2005Customer database Ramezan, 2011Ortiz, 2009;Beattie & Thomson, 2007 Customer retention rate Han & Han, 2004;Kim et al, 2010 Customer satisfaction Tai & Chen, 2009;Han & Han, 2004;Beattie & Thomson, 2007;Cabrilo et al, 2009;Kim et al, 2010;Wall, 2005 Customer service capability Ramezan, 2011 customer's needs Identifying Beattie & Thomson, 2007;Customers ,Tai & Chen, 2009Han & Han, 2004;Beattie & Thomson, 2007;Guthrie & Petty, 2000;Singh & Kansal, 2011;Wall, 2005 New strategic customers Beattie & Thomson, 2007 Unit sales to customer Average revenue per unit Cabrilo et al, 2009;Han & Han, 2004Patients Peng et al, 2007 Stakeholders Knowledge/acquaintance with community …”
Section: Chu Et Al 2006mentioning
confidence: 99%
“…It includes assessment of the stored knowledge value , the cycle of liquid capital , as well as accounting of administration expenses". IT Beattie & Thomson, 2007;Rudez & Mihalic, 2007;Cabrito et al, 2009 Systems information/network Beattie & Thomson, 2007;Tai & Chen, 2009;Singh & Kansal, 2011;Guthric & Petty, 2000;Peng et al, 2007;Kim & Kunter , 2009;Wall, 2005Organizational learning Beattie & Thomson, 2007Peng et al, 2007;Kim & Kunter, 2009 Intellectual Property Kim & Kunter, 2009;Peng et al, 2007;Bozbura & Beskes, 2007 4. Conclusions mentioned, the components of intellectual capital indicate firm future value and the ability to generate financial results.…”
Section: Chu Et Al 2006mentioning
confidence: 99%
“…The company has focused primarily on the disclosure (Sonnier et al, 2008;Singh and Kansal, 2011;Branswijck and Everaert, 2012) of their brands (ISD 3 to ISD 7 ) and strategic alliances (ISD 12 to ISD 14 ), although none procedure has been implemented to measure, recognize those intangibles in the financial reports (Koza and Lewin, 2000;Seethamraju, 2003;Chang et al, 2005). It has followed a strategy based on the voluntary disclosure of information.…”
Section: Intellectual Sustainability Strengthsmentioning
confidence: 99%
“…Relating its dissemination, those resources have been capitalized and included in the organizations' balance sheets (in the cases supported by international accounting standard 38) or reported through complementary statements (intellectual capital reports, programs, scoreboards, ratios, qualitative approaches). Those measurement and disclosure approaches (Sonnier et al, 2008;Singh and Kansal, 2011;Branswijck and Everaert, 2012) tend to complement the traditional financial statements (balance sheet, profit and loss account, cash flows statements), providing a more comprehensive and integrated view of the factors that potentially create economic returns.…”
Section: Introductionmentioning
confidence: 99%